Pemberdayaan Petani Berbasis PGPR untuk Meningkatkan Produktivitas Kangkung di Lahan Gambut Desa Pulau Semambu - Mulawarman, Mulawarman; Arinafril; Anton Meilus Putra; Nurlaili Habibi Danata; Rahmad Fadli (LOSARI DIGITAL, 2026)
Water spinach cultivation in Pulau Semambu Village, South Sumatra, still encounters several constraints, including low productivity, pest and disease attacks, and limited use of biological agents to support sustainable production. This community service program aimed to strengthen farmers’ capacity by introducing practical knowledge and skills in producing and applying locally sourced Plant Growth Promoting Rhizobacteria (PGPR) within a healthy cultivation system. The activities were implemented through four participatory stages: socialization of PGPR concepts and healthy farming practices, training on PGPR production, on-farm demonstration (demonfarm) of its application, and monitoring and evaluation of plant growth and farmer responses. Evaluation results indicated an 85% increase in participants’ knowledge and skills. PGPR application improved plant height, leaf number, and overall vigor of water spinach while reducing pest and disease symptoms. The program demonstrates that participatory training combined with demonfarm effectively facilitates PGPR technology adoption to support environmentally friendly and sustainable water spinach production.